METODE PENAFSIRAN IBN AL-‘ARABî DALAM AHKâM AL-QUR’âN - Fahmi, Saiful (Program Studi Perbandingan Agama, Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri (UIN) Sunan Ampel Surabaya, 2013)
This paper will explain the concept of ontological Ibn al-?Arabi of interpretation, the general idea of the book Ahkâm al-Qur?ân that includes methods, patterns, sources of interpretation, interpretation elements and characteristics that distinguish it from the interpreters other. Ontological view regarding the interpretation that was never a logical consequence of the importance of the final carry was critical of the existing interpretation of the results so far, so it is legitimate to question whether Ahkâm al-Qur?ân is still relevant to the demands of his time or not? Whether in it there is coercion-coercion and preconceptions-ideological Ibn al-?Arabî or not? Given, Ahkâm al-Qur?ân is reproduced in the 5th century AH, where the fight discourse between the schools of thought Islam was at its height. While Ibn al-?Arabi is an intellectual who embrace genuine Mâlikî School, so it brought the prejudice that he is stuck in an ideological reason